The Cambridge companion to Sartre - Howells, Christina (Cambridge University Press, 1992)
This is one of the most comprehensive and up-to-date surveys of the philosophy of Sartre, by some of the foremost interpreters in the United States and Europe. The essays are both expository and original, and cover Sartre's writings on ontology, phenomenology, psychology, ethics, and aesthetics, as well as his work on history, commitment, and progress; a final section considers Sartre's relationship to structuralism and deconstruction. Providing a balanced view of Sartre's philosophy and situating it in relation to contemporary trends in Continental philosophy, the volume shows that many of the topics associated with Lacan, Foucault, Levi-Strauss, and Derrida are to be found in the work of Sartre, in some cases as early as 1936. A special feature of the volume is the treatment of the recently published and hitherto little studied posthumous works.